Retrobulbar versus circumferential subconjunctival anesthesia on the pain control during planned extracapsular cataract extraction with intraocular lens implantation: a randomized equivalence trial - Wasee Tulvatana (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 2003